Some remarks on the phenomenon of Islamic revivalism - Cornelia Löffler-Lohmar (Intereconomics, 1983)
There are several indications that in at least some parts of the Islamic world a process of cultural and political change has begun, with the tendency towards a reassertion of Islamic values. Amongst other things, this involves formulating a concept of modern Islamic economics, the principles of which are derived from the ethical norms of Islam. Is a specifically Islamic economy really likely to develop? What form might this take?
Keywords: 330; Islamic Economics